Adherence to Antituberculosis Drugs in Children and Adolescents in A Low-Endemic Setting: A Retrospective Series. Issue 6 (June 2017) - Guix-Comellas, Eva-Maria; Rozas, Librada; Velasco-Arnaiz, Eneritz; Morín-Fraile, Victoria; Force-Sanmartín, Enriqueta; Noguera-Julian, Antoni
Abstract : Adherence to antituberculosis drug regimens is critical for the prevention and treatment of tuberculosis in pediatrics. In a large retrospective series of children and adolescents in Barcelona, Spain, completion of treatment was worse among patients treated for latent infection, compared with those treated for active tuberculosis or receiving primary chemoprophylaxis. Toxicity and cultural and language barriers were identified as predictors of nonadherence. Abstract : Supplemental Digital Content is available in the text.